System monitoring Soil PH moisture based IoT - Mutammimul Ula; Ezwarsyah Ezwarsyah; Mochamad Ari Saptari; Bakhtiar Bakhtiar; T Multazam (Brilliance: Research of Artificial Intelligence, 2025)
Soil moisture is a water content that wets the soil pores either partially or completely. So far, the process of checking soil moisture is still done manually, where farmers must come directly to the field. To help the process of checking soil pH, this researcher designed and built a soil pH moisture monitoring system based on the Internet of Things which aims to facilitate the process of monitoring the results of soil values ??including pH and moisture levels. In implementing the development of this monitoring system, it was designed using a soil moisture sensor and pH sensor integrated with an Internet of Things (IoT)-based platform, allowing users to monitor soil conditions in real-time via mobile or web applications. With accurate and continuous data, farmers can take quick steps in irrigating and amending soil pH, thereby increasing plant productivity and maintaining soil health. This system implements an Arduino UNO microcontroller, transmitter, YL-69 soil moisture sensor, and LCD as part of the soil monitoring system. Based on the results of the design and testing of this soil moisture monitoring system, users can get information on the condition of the soil pH moisture content. The test results show that this system has high measurement accuracy and easy data access, making it a potential solution to support sustainable agriculture.